Food Studies Matter, Meaning, Movement - Szanto, David; Di Battista, Amanda; Knezevic, Irena (Open textbook library., 2022)
Food Studies aims to help readers understand and address numerous issues within food, food culture, and food systems. These subjects transcend disciplinary boundaries and call attention to how matter, meaning, and movement produce complex and dynamic food-human realities. Chapters range from sovereignty to breastfeeding, financialization to food porn, pollination to fair trade. Embedded throughout, art, poetry, illustration, and audiovisual works offer moments to reflect on and synthesize the text-based entries. Through reading, classroom discussion, and engaging with the extensive pedagogical tools, learners and teachers alike may acquire a new sense of things foodish—along with a new sense of their own place and role within food systems themselves.